A hybrid‐3D hillslope hydrological model for use in Earth system models. Issue 10 (17th October 2015) - Hazenberg, P.; Fang, Y.; Broxton, P.; Gochis, D.; Niu, G.‐Y.; Pelletier, J. D.; Troch, P. A.; Zeng, X.
Abstract: Hillslope‐scale rainfall‐runoff processes leading to a fast catchment response are not explicitly included in land surface models (LSMs) for use in earth system models (ESMs) due to computational constraints. This study presents a hybrid‐3D hillslope hydrological model (h3D) that couples a 1‐D vertical soil column model with a lateral pseudo‐2D saturated zone and overland flow model for use in ESMs. By representing vertical and lateral responses separately at different spatial resolutions, h3D is computationally efficient. The h3D model was first tested for three different hillslope planforms (uniform, convergent and divergent). We then compared h3D (with single and multiple soil columns) with a complex physically based 3‐D model and a simple 1‐D soil moisture model coupled with an unconfined aquifer (as typically used in LSMs). It is found that simulations obtained by the simple 1‐D model vary considerably from the complex 3‐D model and are not able to represent hillslope‐scale variations in the lateral flow response. In contrast, the single soil column h3D model shows a much better performance and saves computational time by 2‐3 orders of magnitude compared with the complex 3‐D model. When multiple vertical soil columns are implemented, the resulting hydrological responses (soil moisture, water table depth, and base flow along the hillslope) from h3D are nearly identical to those predicted by the complex 3‐D model, but still saves computational time. As such, the computational efficiency of the h3D model provides a valuable and promising approach to incorporating hillslope‐scale hydrological processes into continental and global‐scale ESMs. Key Points: This study presents a hybrid‐3D model for the hillslope hydrological response Hydrological simulations are similar to those predicted by a 3‐D Richards model The hybrid‐3D model is computationally 2‐3 orders of magnitude more efficient